Sporting Mega-Events and South-to-South Security Exchanges: A Comparative Study of South Africa and Brazil - McMichael, Christopher (The Hague Journal of Diplomacy, 2013)
The FIFA World Cup and the Summer Olympics are the most prestigious major sporting events in the world, and host governments implement security measures to match this stature. While global concerns about terrorism have led to a dramatic upsurge in the extent of security measures, the perceived threat of urban crime is becoming an increasingly prominent cause for apprehension. This has been of particular importance to South Africa’s recent 2010 World Cup and for the unprecedented sequential hosting of both the 2014 World Cup and the 2016 Olympics in Brazil. In both contexts, security has been used as a statement of intent: the respective states have instrumentalized mega-events as an international platform to signal their ability to secure urban environments. This article will focus on a comparative study of areas in which the respective security preparations for the World Cup in Brazil have overlapped with the measures deployed in South Africa. Using examples of how Brazilian authorities have sought advice from their South Africa counterparts, it will suggest that both countries have adopted comparable risk aversion strategies.
Keywords: South Africa || Brazil || 2010 World Cup || 2014 World Cup || 2016 Olympics || Crime || Police || Militarization